The Relationship Between Corruption and Income Inequality in U.S. states: Evidence From a Panel Cointegration and Error Correction Model - Apergis, Nicholas; Dincer, O.; Payne, J. (Springer New York LLC, 2010)
We investigate the causality between corruption and income inequality within a multivariate framework using a panel data set of all 50 U.S. states over the period 1980 to 2004. The heterogeneous panel cointegration test by Pedroni (Oxf. Bull. Econ. Stat. 61:653–670, 1999; Econom. Theory 20:597–627, 2004) indicates that in the long run corruption and the unemployment rate have a positive and statistically significant impact on income inequality while a negative impact is found for real personal income per capita, education, and unionization rate. The Granger-causality results associated with a panel vector error correction model indicate both short-run and long-run bidirectional causality between corruption and income inequality.